Deficits in odor discrimination versus odor identification in patients with schizophrenia and negative correlations with GABAergic and DNA methyltransferase mRNAs in lymphocytes - Smith, Robert C.; Sershen, Henry; Youssef, Mary; Lajtha, Abel; Jin, Hua; Zhang, Mumei; Chen, Anmei; Guidotti, Alessandro; Davis, John M. (Frontiers in Psychiatry, 2023)
People with schizophrenia have been reported to show deficits in tests of olfactory function. DNA methylation and GABAergic input have been implicated in biochemical processes controlling odor in animal studies, but this has not been investigated in human studies. In a study of measures of DNA methylation and GABAergic mRNAs in lymphocytes we also measured odor identification and discrimination with the Sniffin’ Sticks battery in 58 patients with chronic schizophrenia (CSZ) and 48 non-psychotic controls (NPC). mRNAs in lymphocytes were assessed by qPCR using TaqManTM probes. Cognition was assessed by the MATRICS battery in CSZ and NPC and symptoms in CSZ were assessed by PANSS scale. The relationships of odor deficits of mRNA, cognition, and symptoms were explored by correlation analysis. Variables which significantly differentiated CSZ from NPC were explored by logistic regression. Overall CSZ showed significantly (P≤.001) lower scores on odor discrimination compared to NPC with a moderate effect size, but no difference in odor identification. Deficits in odor discrimination, which has not been standardly assessed in many prior studies, strongly differentiated CSZ from NPC. In logistic regression analysis odor discrimination, but not odor identification, was a significant variable predicting schizophrenia versus control class membership. This is the first study to report relationship between odor deficits and methylation and GABAergic mRNAs in blood cells of human subjects. There were negative correlations of odor identification with DNA methylation enzymes mRNAs and significant negative correlations with odor discrimination and GABAergic mRNAs. Lower odor scores were significantly associated with lower cognitive scores on the MATRICS battery in CSZ but not NPC subjects. In CSZ lower odor scores were significantly associated with negative symptom scores while higher odor identification scores were associated with PANNS Excitement factor.